The History Of Islamization In Indonesia: Its Dynamics And Development - Azman, Zainal; Supriadi, Supriadi (El-Ghiroh : Jurnal Studi Keislaman, 2025)
The introduction of Islam to Indonesia is a complex historical event that occurred over an extended period, beginning in the 7th century and reaching its peak from the 13th to the 16th century. There are five theories regarding the entry of Islam into the archipelago, primarily based on the origin of its bearers: the Arab theory, the Chinese theory, the Persian theory, the Indian theory, and the Turkish theory. This research employs a literature study with a qualitative approach. The strategies for spreading Islam in the archipelago were carried out through trade routes, preaching (dawah), marriage, education, and cultural Islamization. The key figures who disseminated Islam in the archipelago were scholars and kings/sultans. Islamization in the archipelago is characterized by its unique features, namely a relatively peaceful and gradual spread, which differs from the pattern of Islamic dissemination in some other regions of the world. Islam was introduced through various channels, especially trade, marriage, and preaching by Muslim traders, scholars, and Sufis. Ports and coastal cities became the initial points of Islamic spread, eventually reaching inland areas. The Islamization process in Indonesia is also marked by intensive adaptation and acculturation with local cultures, resulting in a distinctive form of Islam unique to the archipelago. This accommodative approach allowed Islam to be widely accepted and to become an integral part of the Indonesian identity. The arrival of Islam not only transformed the religious landscape but also shaped new social, political, and cultural dynamics, which have had a profound and lasting influence on the formation of Indonesia's national identity.